2011
DOI: 10.1186/1748-717x-6-154
|View full text |Cite
|
Sign up to set email alerts
|

Mixed modality treatment planning of accelerated partial breast irradiation: to improve complex dosimetry cases

Abstract: BackgroundAlthough 3D-conformal accelerated partial breast irradiation (APBI) is widely used, several questions still remain such as what are the optimal treatment planning modalities. Indeed, some patients may have an unfavorable anatomy and/or inadequate dosimetric constraints could be fulfilled ("complex cases"). In such cases, we wondered which treatment planning modality could be applied to achieve 3D-conformal APBI (2 mini-tangents and an "en face" electron field or non-coplanar photon multiple fields; o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The dosimetry of IMRT and VMAT over the standard conformal technique has been analysed in several studies [12,[26][27][28][29][30][31]. The use of inverse treatment planning improved conformity and, in most cases, also the exposure of selected risk organs decreased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dosimetry of IMRT and VMAT over the standard conformal technique has been analysed in several studies [12,[26][27][28][29][30][31]. The use of inverse treatment planning improved conformity and, in most cases, also the exposure of selected risk organs decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the rising number of patients needing APBI, and to eliminate the special infrastructural and expertise needs of brachytherapy, the implementation of conformal teletherapy methods, such as 3D-conformal radiation therapy (3D-CRT) with multiple static photon and/or electron fields, intensity-modulated RT (IMRT), volumetric-modulated arc therapy (VMAT), tomotherapy, robotic radiosurgery systems and proton beam therapy has begun emerging [8][9][10][11]. The utilization of a mixed technique combining photon with an 'en face' electron field may result in improved planning target volume (PTV) coverage and organ at risk (OAR) exposure [10][11][12][13][14]. IMRT optimizes dose distribution using structure-based planning and alterable intensity beam fluencies, providing improved dose homogeneity within the PTV, and reduced high dose exposure of normal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…In certain PBI cases, the dose distribution and OAR exposure may be optimized by the combination of photon and electron fields. [23][24][25] Only 1 contemporary study has reported the use of sole electron fields for PBI. 26,27 Altogether 40 patients with relatively small breasts received electron irradiation of a dose of 25 Â 2 Gy; this technique resulted in the lowest rate (17.5%) of fat necrosis of grade I to III, as compared with that in the brachytherapy and WBI arms.…”
Section: Clinical Outcomementioning
confidence: 98%
“…The addition of electrons to photon beams provides more conformal but less homogenous dose distribution as compared to the photon only technique. We have found five studies dealing with the mixed beam technique in APBI [83,[90][91][92][93]. All agreed that this approach may lower the ipsilateral breast dose; lung and heart doses varied according to study, and obviously the situation of the tumour bed [92].…”
Section: Dosimetric Comparison Of 3d-crt Sliding Window Imrt and Vmamentioning
confidence: 98%
“…Many studies analysed the dosimetry of inverse-planning techniques over standard 3D-CRT [83][84][85][86][87][88]. The use of IMRT or VMAT improved conformity in all studies, and in most of them selected OARs' exposure as well.…”
Section: Dosimetric Comparison Of 3d-crt Sliding Window Imrt and Vmamentioning
confidence: 99%